Surface effects after a combination of dental bleaching and enamel microabrasion: An in vitro and in situ study - Franco, Laura Molinar [UNESP]; Machado, Lucas Silveira [UNESP]; Salomão, Fabio Martins [UNESP]; Dos Santos, Paulo Henrique [UNESP]; Briso, André Luiz Fraga [UNESP]; Sundfeld, Renato Herman [UNESP] (Japanese Society for Dental Materials and Devices, 2016)
This study evaluated the effects of combining enamel microabrasion and dental bleaching on the physical properties of enamel, using in vitro and in situ conditions and evaluating surface roughness, enamel microhardness and scanning electron microscopy images. One hundred sound bovine teeth were sectioned and cut into discs and randomly divided into 10 study groups (n=10). The results were submitted to Analysis of Variance (ANOVA) for repeated measures, followed by the Tukey test, with significance at 5%. Enamel surface roughness was significantly influenced by microabrasion, regardless of being combined with dental bleaching, for both HS (Human Saliva) or AS (Artificial Saliva) condition. Enamel microhardness was significantly decreased in the groups in which enamel microabrasion was performed, regardless its combination with dental bleaching; although storage in HS reestablished the initial enamel microhardness. It was concluded that dental bleaching does not cause major damage to microabraided enamel, and that only human saliva recovered the initial enamel microhardness.
Keywords: Dental enamel; Electron microscopy; Microhardness test